Development of highly discriminatory SCoT- and CBDP-based SCAR fingerprint for authentication of Indian senna (Senna alexandrina Mill.) formerly Cassia angustifolia Vahl.) - Chouksey, Sarika; Ashfaq, Mohd Ashraf; Kaira, Pushkar; Farhat, Sabnam; Pandey, Maneesha; Kumar, Ch. Anil; Nagaraja Reddy, Rama Reddy (Frontiers in Plant Science, 2024)
Indian senna (Senna alexandrina Mill.) (formerly Cassia angustifolia Vahl.) is an important medicinal plant of the family Fabaceae. The leaves and pods of Indian senna yield sennosides and rhein-based laxative. Adulteration of Indian senna is a serious issue as with most of the medicinal plants used in the Indian systems of traditional medicine. The bulk of dried leaves and pods of morphologically related species such as Cassia fistula, Senna occidentalis, Senna sophera and Senna tora is usually mixed with those of the Indian senna and the admixture is used in laxative based formulations. The present investigation is a modest attempt at developing species-specific Start Codon Targeted Polymorphism (SCoT) and CAAT-Box Derived Polymorphism (CBDP) based Sequence Characterized Amplified Region (SCAR) markers for the identification and authentication of Indian senna and four adulterant species (C. fistula, S. occidentalis, S. sophera and S. tora species). In this study, genomic DNA extracted from 44 accessions of Indian senna and four adulterant species was subjected to SCoT and CBDP PCR. The polymorphic amplicons were identified, eluted, ligated and transformed into E. coli DH5 α strain. PCR, restriction analysis and DNA sequencing confirmed the transformed recombinant plasmid clones. Post-sequencing, the sequence of the primary SCoT and CBDP primers was analysed and extended into the unique signature sequence of the concerned accessions. This resulted in development of one SCoT-44 based and two CBDP-25 based SCARs. SCoT-44 SCAR produced a signature amplicon of 287 bp for accession DCA120 and CBDP-25 SCAR yielded signature amplicons of 575 bp and 345 bp for accessions DCA13 and DCA119 respectively. The developed SCAR markers were validated across 48 samples (44 accessions of Indian senna and 4 adulterant species) and yielded distinct amplicons in Indian senna only, while no such amplicon was observed in the other four adulterant species. The information generated using these markers have been faithfully converted to single-locus, unequivocal, highly reproducible and informative sequence-based SCAR markers. These markers will enable discrimination of individual plants on the basis of unique sequence specific amplicons which could be used as diagnostic markers to settle issues pertaining to the true identity of Indian senna.